"A cute surprise": Examining the influence of meeting giveaways on word-of-mouth intention. (December 2020) - Sun, Jie; Nazlan, Nadia Hanin; Leung, Xi Yu; Bai, Billy
Abstract: Although most meetings offer free giveaways to attendees, the role these giveaways plays in influencing attendees' behavioral intentions has received limited attention. This study contributes to event research by examining the impact of giveaways on meeting attendees' word-of-mouth (WOM) intention. Two 2 × 2 between-subjects experimental designs were utilized for this study. Results showed that high-value giveaways lead to greater WOM intention among meeting attendees compared to low-value giveaways. Moreover, the study found that cuteness and experienced unexpectedness moderate the effect of meeting giveaways' value on attendees' WOM intention. Theoretical and practical implications are discussed.